2018
DOI: 10.1080/08985626.2018.1514074
|View full text |Cite
|
Sign up to set email alerts
|

Familial relationships and firm performance: the impact of entrepreneurial family relationships

Abstract: While the family may serve as a resource for entrepreneurs, it has been studied separately in different disciplines. In this paper, we combine the arguments on familial relationships (family firm literature) and skill variety (regional learning literature) to analyse how different forms of entrepreneurial family relationships (co-occurrences) facilitate firm performance, and how familial relationships moderate the effects of skill variety on firm performance. Using longitudinal data (2002-2012) on a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 67 publications
(108 reference statements)
3
21
0
Order By: Relevance
“…Even though the current study did not separate family from non-family SMEs, its results could not sustain the aforementioned tendencies. In fact, in line with a recent study by Adjei et al (2019), spouses and children showed a positive relationship with business performance.…”
Section: Discussionsupporting
confidence: 89%
“…Even though the current study did not separate family from non-family SMEs, its results could not sustain the aforementioned tendencies. In fact, in line with a recent study by Adjei et al (2019), spouses and children showed a positive relationship with business performance.…”
Section: Discussionsupporting
confidence: 89%
“…Leiva Alegre & Monge 2014; Paltasing 2012) concurred that entrepreneurial education/learning is a lifelong learning process. All the accumulated knowledge that a person has gained throughout his or her life can contribute to setting up a new firm (Adjei et al 2019). Efforts of entrepreneurial education can include learning from entrepreneurs' positive and negative experiences (Pagano, Petrucci & Bocconcelli 2018).…”
Section: Entrepreneurial Education and Skillsmentioning
confidence: 99%
“…There is the responsibility for keeping staff as in Case 1, but the citizenship (cf. Adjei et al 2018) expressed in interactivities goes further through promoting the region to raise its attractiveness and make people move into the region. This again results in an interactivity with other firms and the municipality as an organization in terms of shared efforts to raise attractiveness of the region, but also development of the firms (through the R&D project engaging also a university).…”
Section: Discussionmentioning
confidence: 99%
“…The context, as described in family firm studies, is largely the social context, inferring kinship and social relations creating legitimacy and status for the family (Anderson, Jack, and Dodd 2005). On the broader definition of the context as a location, the heritage of being locally founded and the citizenship mean that the family firm would integrate with the region (Adjei et al 2018;Berrone et al 2010;Bjuggren, Johansson, and Sjögren 2011). Traditions and the heritage of being founded in the region would make the firm less inclined to change location, and there would be a strong dependability on local resources and individuals for recruitment, also woven into how a family firm expectedly would be risk averse and rather keep with the present and past than change company focus or location, let alone expand or internationalize.…”
Section: Framing the Topic Of Family Firms And Their Contextmentioning
confidence: 99%
See 1 more Smart Citation